Mechanical properties of C-S-H globules and interfaces by molecular dynamics simulation. (10th July 2018) - Fan, Ding; Yang, Shangtong
Highlights: The mechanical properties for the 4.2 nm C-S-H globules are determined. The interfacial properties between C-S-H globules are examined with different water. The results shed lights on meso-scale modelling of C-S-H by providing essential inputs. Abstract: At meso-scale, Calcium Silicate Hydrate (C-S-H) can be considered as randomly packed globules (about 4.2 nm), which forms the basic unit cell, with water molecules and voids. In this paper, the nanostructures for the globules are developed based on some plausible atomic structures of C-S-H. The mechanical properties for the C-S-H globules are determined through molecular dynamics simulation. Interfaces between the C-S-H globules are also simulated with different amount of water molecules. Key material parameters, e.g., Young's modulus, strength and fracture energy, are obtained. It has been found that longer mean chain length of silicate tends to increase the strength of C-S-H and change the fracture behavior from brittle to ductile failure, in the chain length direction. In the other direction, however, silicate chains do not play an important role while interlayer structure matters. Moreover, pores in the C-S-H nanostructures can considerably reduce the strength of the globule structures in the normal direction to silicate chain but the weakening effect becomes substantially less in silicate chain direction. Further, it has been found that for all types of the interfaces between C-S-H globules, the interface with no extra water molecules has the greatest tensile/shear strength. The mechanical properties obtained in this paper for C-S-H nanostructures and interfaces could be necessary inputs to the meso-scale modelling of C-S-H via either granular mechanics, i.e., DEM, or continuum mechanics, i.e., FEM.